Kajian Dampak Pencemaran Terhadap Kualitas Lingkungan Perairan dan Struktur Komunitas Organisme Makrozoobenthos Di Muara Sungai Babon, Semarang - Muh. Yusuf (Universitas Diponegoro, 2011)
Abstract The research was done to know: (1) the condition of waters quality, (2) community structure of macrozoobenthos of estuarine of Babon river of Semarang. The research method is case study. Sampling was done three times, with the time interval between 14-15 days. The re research was done from April until November, 2005 at estuarine of babon river, Genuk District, Semarang City. Based on the result of measurement of physical-chemical paremeters showed that several parameter include : total suspended solid, oxygen, BOD5, COD, ammonia, deterjen, and heavy metal Cr6+ and Cd have passed over sea water quality standard. The diversity index (H’) range from low to middle that is between 0,36 – 2,27. Whereas the equatability indeks (E) range from low to high that is between 0,33 – 0,96. Key words : waters quality, community structure, macrozoobenthos